Study of cardiac manifestations in patients with chronic liver disease - K. R., Divya Sharma; T., Kavya S. (International Journal of Advances in Medicine, 2019)
Background: Chronic liver disease is a common cause of mortality and morbidity worldwide. This has pathological effects on various systems in the body including cardiovascular system which usually is unnoticed. In majority of cases of chronic liver disease, cardiovascular complications develop as a subclinical condition which manifests only during stressful situations. Hence early detection of cirrhotic cardiomyopathy by echocardiography and 2D-ECHO studies in all patients of chronic liver disease helps in reducing the morbidity and mortality. Methods: 100 cases of chronic liver disease were included in the study. Data was collected through a prepared proforma. All patients were subjected to cardiac evaluation by ECG and Echocardiography. Serum pro-BNP levels were done for selected patients. Severity of the liver disease was assessed by using Child-Pugh score. Cardiac abnormalities were noted and correlated with the severity of the liver disease. Results: Out of 100 patients studied, 83% were males. 80% of the patients had history of alcoholism. 59% of the patients had abnormal ECG finding. 40% of them had QT prolongation and was related to the severity of liver disease. 60% of the total patients studied had positive pro-BNP values in patients with significant cardiac dysfunction. 46% of the patients had normal echocardiographic finding; most common abnormal finding was diastolic dysfunction (43%) and positively correlated with severity of liver disease. Conclusions: In chronic liver disease patient’s QT prolongation is the most common ECG abnormality. Most common Echocardiographic finding was diastolic dysfunction which had strong correlation with the severity of the liver disease.